1979
DOI: 10.1093/ajcp/71.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Increase of IgA-bearing Lymphocytes in Peripheral Blood from Patients with IgA Nephropathy

Abstract: Aberration of IgA-bearing B lymphocytes in patients with IgA nephropathy has been investigated. Twelve patients with IgA nephropathy demonstrated a marked increase of IgA-bearing lymphocytes in peripheral blood, while ten patients with chronic proliferative glomerulonephritis without mesangial deposition of IgA showed normal amounts of IgA-bearing lymphocytes. The increase of IgA-bearing lymphocytes reflected that of IgA-producing lymphocytes, since lymphocytes obtained from patients with IgA nephropathy resto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 4 publications
4
27
0
Order By: Relevance
“…In this regard, the existence of high serum levels of polymeric IgA [5], probably due to their elevated production by peripheral stimulation [6], has been demonstrated. Furthermore, a selective increase in IgA-bearing peripheral blood lym phocytes [7], a decrease of IgA-specific suppressor T cell activity [8. 9], and an IgA-specific increased activity of T helper cells have been recently shown [10], The role of all these immune cell abnormalities in the appearance and development of the IgA nephropathy is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the existence of high serum levels of polymeric IgA [5], probably due to their elevated production by peripheral stimulation [6], has been demonstrated. Furthermore, a selective increase in IgA-bearing peripheral blood lym phocytes [7], a decrease of IgA-specific suppressor T cell activity [8. 9], and an IgA-specific increased activity of T helper cells have been recently shown [10], The role of all these immune cell abnormalities in the appearance and development of the IgA nephropathy is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There is some debate regarding the cause of the deposition. Several investigators have proposed that the elevation of the serum IgA1 concentration is the cause of IgAN (24,26). To explain why IgA1, but neither IgA2 nor IgG is deposited, it was proposed that O-glycan structures in the hinge region of IgA1 are profoundly involved in the deposition.…”
mentioning
confidence: 99%
“…We reported earlier [30] increased levels of such IgA-bearing lympho cytes in peripheral blood in patients with IgA nephropa thy, while Fiorini et al [31] and Cosio et al [32] reported normal levels. Deviations among these reports could be eliminated by using fluorescent-activated cell sorters which eliminate any variations among individual observ ers using automated cell counting [27].…”
Section: Dr H Sakaimentioning
confidence: 66%